Tolerance to 2,4-dinitrofluorobenzene-induced contact hypersensitivity is mediated by CD73-expressing tissue-homing regulatory T cells - Da, Meihong; Chen, Luxia; Enk, Alexander; Mahnke, Karsten (The journal of investigative dermatology, 2023)
Regulatory T cells (Tregs) express CD73, an ectonucleotidase that converts adenosine (Ado) monophosphate to Ado, which has been shown to suppress immune reactions. To investigate the role(s) of CD73+ Tregs during the induction of tolerance, we used a 2,4-dinitrofluorobenzene‒driven contact hypersensitivity model, in which tolerance can be induced by pretreating wild type mice with 2,4-dinitrothiocyanobenzene. CD73-deficient mice were unable to acquire tolerance. Likewise, transfer of CD73‒/‒ Tregs failed to suppress 2,4-dinitrofluorobenzene‒induced ear swelling in wild type mice, whereas transfer of wild type‒derived Tregs into CD73‒/‒ mice re-established tolerance. This indicates a crucial role of CD73+ Tregs for skin-induced tolerance. Furthermore, we found that 2,4-dinitrothiocyanobenzene induces more activated CD73+ tissue-homing Tregs (marked by Ki-67, CTLA4, CCR4, CD103, CCR6, and CD49b expression) in draining lymph nodes and blood, eventually accumulating in the skin. The application of anti-CD73 antibodies that block CD73-derived Ado production as well as the injection of Ado deaminase, which degrades Ado in tissues, abrogated tolerance induction. Thus, our data indicate that CD73+ Ado-producing Tregs are crucial for the regulation of contact hypersensitivity reactions and tolerance induction in the skin and that manipulating the function(s) of CD73 in tissues may offer a tool to influence autoimmunity and inflammation in vivo.
Online verfügbar 17. Dezember 2022, Artikelversion 19 May 2023
Gesehen am 20.07.2023